2021
DOI: 10.1055/s-0040-1721686
|View full text |Cite
|
Sign up to set email alerts
|

Two Missense CACNA1A Variants in a Single Family with Variable Neurobehavioral, Cerebellar, Epileptic, and Oculomotor Features

Abstract: We describe two novel missense variants in CACNA1A segregating in a family with variable severity of ataxia/oculomotor dysfunction, neurobehavioral impairments, and epilepsy. The most severe outcome occurred in a compound heterozygous proband, which could represent variable expression of the paternal allele or biallelic modulation of calcium channel function. Acetazolamide and lamotrigine were effective for seizure control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Family members with heterozygous variants manifested ID and ataxia. A similar patient has since been reported (Ko et al, 2021 ). Recently, a CACNA1A homozygous truncating variant (p.Arg932*) was reported in a consanguineous family.…”
Section: Introductionsupporting
confidence: 77%
“…Family members with heterozygous variants manifested ID and ataxia. A similar patient has since been reported (Ko et al, 2021 ). Recently, a CACNA1A homozygous truncating variant (p.Arg932*) was reported in a consanguineous family.…”
Section: Introductionsupporting
confidence: 77%
“…On review of the latest literature in the EA, published since the closing date of our initial systematic literature review (April 2021–June 2022), we identified a total of nine related articles (Table S4). These reported on 10 patients with novel variants in the CACNA1A [19–29]. In a case report of CACNA1A ‐related EA, dalfampridine 0.3 mg/kg was shown to resolve falls that had been unresponsive to acetazolamide (treatment was delayed due to insufficient literature on the topic) [30].…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the latest literature (April 2021–June 2022) revealed a total of two related articles (Table S4). These were reported on two patients with novel variants in the PDHA1 gene [19–29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation